Gender and the Use of Hedges in Doctoral Theses Writing: Evidence from a Ghanaian University - Shirley Eli Banini; Ramos Asafo-Adjei; Ernest Kwesi Klu (E-Journal of Humanities, Arts and Social Sciences)
This academic writing-based study turns its attention to analysing the gender-based use of hedges in doctoral theses written in the Humanities at the University of Ghana. The study aimed to answer the research question: What are the gender-based uses of hedges in the doctoral theses at the University of Ghana? Using the simple case study design, the Literature Review (LR) chapters of forty (40) theses written by doctoral students over five academic years were purposively selected from the College of Humanities were analysed using Ken Hyland’s (2005) hedging device categorisations. The analyses reveal the utilisation of different types of hedges, namely: modal auxiliary verbs, adverbials, adjectives and approximators. Males used more modal auxiliary verbs than females. A similar trend was registered for approximators, adverbials, introductory verbs, adjectives and probability adjectives. It was concluded that there are gender differences in the number of hedging devices used by males, compared to their female counterparts. It is recommended that lecturers handling English language, Academic Literacy (Communication Skills) and Research Methodology should train students more on applying hedges to achieve more impactful writing. This study contributes to scholarship by highlighting the gendered use of hedges within the Ghanaian higher education space – a basis for enhanced andragogical approaches in language research and supervision.